TcG2/TcG4 DNA Vaccine Induces Th1 Immunity Against Acute Trypanosoma cruzi Infection: Adjuvant and Antigenic Effects of Heterologous T. rangeli Booster Immunization - Gupta, Shivali; Salgado-Jiménez, Berenice; Lokugamage, Nandadeva; Vázquez-Chagoyán, Juan Carlos; Garg, Nisha Jain (Frontiers in Immunology, 2019)
Background: Chagas cardiomyopathy is caused by Trypanosoma cruzi (Tc). Two antigenic candidates, TcG2 and TcG4, are recognized by antibodies in naturally infected dogs and humans; and these vaccine candidates provided protection from Tc infection in mice and dogs. Trypanosoma rangeli (Tr) is non-pathogenic to mammals and shown to elicit cross-reactive anti-Tc antibodies. In this study, we investigated if fixed Tr (fTr) can further enhance the efficacy of the TcG2/TcG4 DNA vaccine. Methods and Results: C57BL/6 mice were immunized with TcG2/TcG4 DNA vaccine and fTr (delivered as an adjuvant or in prime-boost approach), and challenged with Tc. Serology studies showed that fTr (±quil-A) elicited Tc- and Tr-reactive IgGs that otherwise were not stimulated by TcG2/TcG4 vaccine only, and quil-A had suppressive effects on fTr-induced IgGs. After challenge infection, TcG2/TcG4-vaccinated mice exhibited potent expansion of antigen- and Tc-specific IgGs that were not significantly boosted by fTr±quil-A. Flow cytometry analysis showed that TcG2/TcG4-induced dendritic cells (DC) and macrophages (M) responded to challenge infection by expression of markers of antigen uptake, processing, and presentation, and production of pro-inflammatory cytokines. TcG2/TcG4-induced CD4+T cells acquired Th1 phenotype and expressed markers that orchestrate adaptive immunity. A fraction of vaccine-induced CD4+T cells exhibited iTreg phenotype responsible for aversion of self-injurious immune responses. Further, TcG2/TcG4-vaccinated mice exhibited potent expansion of poly-functional CD8+T cells with TNF-α/IFN- production and cytolytic phenotype post-infection. Subsequently, tissue parasites and pathology were hardly detectable in TcG2/TcG4-vaccinated/infected mice. Inclusion of fTr±quil-A had no clear additive effects in improving the Tc-specific innate and adaptive immunity and parasite control than was noted in mice vaccinated with TcG2/TcG4 alone. Non-vaccinated mice lacked sufficient activation of innate immune cells and Th1 CD4+/CD8+T cells, and exhibited >10-fold higher levels of tissue parasite burden than was noted in vaccinated/infected mice. Conclusion: TcG2/TcG4 vaccine elicits highly effective innate/adaptive immunity, and inclusion of fTr is not required to improve the efficacy of DNA vaccine against acute Tc infection